MODEL OF AUTHENTIC ENGLISH TEACHING MATERIAL FOR LAW FACULTY STUDENTS - Syahrial Syahrial (Proceedings of ISELT FBS Universitas Negeri Padang, 2017)
In recent years in line with identifying needs and wants of groups of students who learn English for either academic purposes (EAP) or job-related purposes (EOP), teachers or lecturers in the field of ESP have felt an onerous responsibility for fostering appropriate materials and methodologies for these students to maximize their learning. This study aimed to develop an effective model of authentic English teaching material (textbook) for law faculty students. This purpose was obtained through model development research. The students of law faculty at Universitas Bengkulu, the lecturers, and lawyers are used as the subjects of this study. The study was carried out in three steps, which are (1) needs identification and curriculum analysis, (2) learning material (textbook) design and development, and (3) textbook evaluation.In the first part, the students’ opinions of their needs and wants are presented based on the analysis of the questionnaires and documentation. This is followed by displaying the theory and the data for the fundamental basis of the second step. Lastly, the material was validated by two experts for the revision and improvement. Then, the material was tried out before gaining the final product. It is to be concluded that material of this kind allows the students to bring their own knowledge of the world to their lessons. At the end of English lesson, the students not only practice English, but also they are better informed about the issue of their field.